Can Air Seat Cushions and Ball Chairs Improved Classroom Behaviors of Students with Autism Spectrum Disorder: A Single Subject Study - Nader Matin Sadr; Hojjat Allah Haghgoo; Sayyed Ali Samadi; Mehdi Rassafiani; Enayatollah Bakhshi (Shiraz University of Medical Sciences, 2015)
Background: Classroom behaviorsare disturbed in autistic students because of their repetitive, restlessness, and disruptive behaviors. This study aimed to examine the impacts of sitting on a ball, cushion, and/or common chair on classroom behavior of four students with Autism Spectrum Disorder (ASD). Methods: Four children with Autism participated in this single-subject study. Students' behaviors were video recorded in three phases: Sitting on their common chairs during phase A, air-sit cushioned in phase B, and ball chairs in phase C. Sitting times and on-task/off-task behaviors were quantified by momentary time sampling (every 10 seconds) and compared during different phases for important changes. Social validity was taken by the teacher at the end of the research as well. Results: The findings demonstrated increases in on-task and in-seat behaviors in four students when seated on air sit cushioned chairs. Despite rises of ontask behaviors for all students, only two of the students showed enhanced inseat behaviors when seated on therapy balls. Social validity findings indicated that the teacher preferred the use of the balls and air-cushioned chairs for her students. Conclusion: Therapy balls/cushioned chairs for students with ASD may facilitate in-seat and on-task behavior.